Quality Control of Photosystem II: The Mechanisms for Avoidance and Tolerance of Light and Heat Stresses are Closely Linked to Membrane Fluidity of the Thylakoids - Yamamoto, Yasusi (Frontiers in Plant Science, 2016)
When oxygenic photosynthetic organisms are exposed to excessive light and/or heat, Photosystem II is damaged and electron transport is blocked. In these events, reactive oxygen species, endogenous radicals and lipid peroxidation products generated by photochemical reaction and/or heat cause the damage. Regarding light stress, plants first dissipate excessive light energy captured by light-harvesting chlorophyll protein complexes as heat to avoid the hazards, but once light stress is unavoidable, they tolerate the stress by concentrating damage in a particular protein in photosystem II, i.e. the reaction-center binding D1 protein of Photosystem II. The damaged D1 is removed by specific proteases and replaced with a new copy produced through de novo synthesis (reversible photoinhibition). When light intensity becomes extremely high, irreversible aggregation of D1 occurs and thereby D1 turnover is prevented. Once the aggregated products accumulate in Photosystem II complexes, removal of them by proteases is difficult, and irreversible inhibition of Photosystem II takes place (irreversible photoinhibition). Important is that various aspects of both the reversible and irreversible photoinhibition are highly dependent on the membrane fluidity of the thylakoids. Heat stress-induced inactivation of photosystem II is an irreversible process, which may be also affected by the fluidity of the thylakoid membranes. Here I describe why the membrane fluidity is a key to regulate the avoidance and tolerance of Photosystem II on environmental stresses.